Karakteristik Italian Meringue Butter Cream Menggunakan Proporsi Pemanis yang Berbeda - Handayani, Ira; Ndaru Prasastono; Karinta Ulayya Bulan Az Zahra (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The objective of this study was to assess the sensory acceptability of Italian Meringue Butter Cream in terms of texture, aroma, color, and taste, using varying proportions of sweeteners. The research was carried out in the Culinary Arts Laboratory of the Ibu Kartini Academy of Social Welfare. An experimental approach was employed, utilizing a Completely Randomized Design (CRD). The study involved three treatments with different ratios of granulated sugar to stevia: F1 (220 g : 20 g), F2 (150 g : 25 g), and F3 (80 g : 30 g). A total of 35 untrained panelists participated in the hedonic sensory evaluation. The resulting data were analyzed using the non-parametric Kruskal-Wallis test, followed by the Mann-Whitney U test at a 95% confidence level (α = 0.05). The findings revealed that the variation in sweetener proportions significantly influenced the panelists’ preferences regarding aroma, texture, color, and taste. Among all formulations, the F1 treatment received the highest level of overall acceptance.